(untitled) (Revista de Ciencias de Seguridad y Defensa, 2023)
The centennial University of the Armed Forces ESPE in accordance with its domains: institutional "Security, Defense and Society" and academic "Security and Defense", trains integral professionals through its chairs: Leadership, National Reality and Geopolitics, these constitute a transversal axis in university education; In this framework, the objective of the article is to analyze the citizen’s perception regarding the university student’s exit profile, and their assessment of whether the training process should include the development of citizen competencies. For this purpose, a survey was applied in a random sample of the population using a questionnaire with closed questions and Likert scales. The results reflected that the majority of citizens consulted positively value the development of citizen competencies in the areas of Peace, Justice and Solid Institutions, as well as the promotion of moral education, leadership, promotion of rights, coexistence, democratic participation and pluralism. It was identified that the citizen dimensions considered adequate in the training process of new professionals include: prevention, knowledge of rights, ethics and morals, as well as inclusive strategic decision making. A documentary review of the regulatory framework in the region was carried out, highlighting that in Colombia the importance of citizen competencies is established for integral human development and the strengthening of democracy.